1991
DOI: 10.2105/ajph.81.11.1494
|View full text |Cite
|
Sign up to set email alerts
|

Age- and sex-specific cycles in United States suicides, 1973 to 1985.

Abstract: Total US suicides peak on the first day of each week, in the first week of each month, and in the late spring of each year. Although these cycles are assumed to characterize all US suicides, analyses by age and sex show that the cycles occur only in a few subpopulations. Day-of-the-week effects are found almost exclusively in middle-aged suicides; day-of-the-month effects are found almost exclusively in elderly male suicides; and month-of-the-year effects asre found almost exclusively in teenaged and elderly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 3 publications
5
38
0
2
Order By: Relevance
“…A similar bimodal distribution with peaks in spring and autumn was also shown to be present in France by Souetre et al [13] , whereas Thompson [14] found an autumn peak for young males in Canada. McCleary et al [17] reported a fall/winter peak among young adolescents under 16 years of age in the USA. Peaks in spring/ summer have also been observed in South Africa [18] and Italy [22] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar bimodal distribution with peaks in spring and autumn was also shown to be present in France by Souetre et al [13] , whereas Thompson [14] found an autumn peak for young males in Canada. McCleary et al [17] reported a fall/winter peak among young adolescents under 16 years of age in the USA. Peaks in spring/ summer have also been observed in South Africa [18] and Italy [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Näyhä [11] suggested that the autumn peak in adolescent suicides might be due to the intensification of social life after the summer vacations, which exposes people to stressful situations. Chew and McCleary [17,35] emphasized the congruence of the autumn peak in suicides among under 16-year-old males and the academic year. They, too, conclude that those poorly integrated into academic society will prefer suicide, when academic life becomes too intense.…”
Section: Discussionmentioning
confidence: 99%
“…While males may predominate in terms of numbers, as a choice suicidal drowning is favoured by females 50 years of age and older in almost all available studies. Seasonal variations in drowning was evident in both sexes with increased frequency in March, April and May not dissimilar to studies from Belgium (Maes et al, 1993), the United States (McCleary et al, 1991) and in Cheshire, UK (Salib and Gray, 1997) but unlike Lunetta et al (2003) who reported higher frequency of drowning in the cold season in Finland.…”
Section: Interpretation Of the Findingsmentioning
confidence: 46%
“…• The paper by McCleary et al [10] was preceded by a paper by MacMahon [9]. Although it does not give monthly data by age-group, it is nevertheless of interest because it gives the monthly pattern in 1972-1978 that is to say some 30 years earlier than the 1999-2007 data represented in Fig.…”
Section: Complementary Observationsmentioning
confidence: 99%
“…9 For some reason, the age-group > 90 is not given in 2005 and 2008. That is why (when we need all 8 years) we will limit ourselves to 15 age-groups 10. On 15 August 2014 the address was the following: http://www.cdc.gov/nchs/nvss/mortality/gmwk306.htm 11.…”
mentioning
confidence: 99%